Do changes in working hours increase stress in Japanese white-collar workers? - Ozawa, Masaki; Anzai, Tatsuhiko; Yamauchi, Takashi; Takahashi, Kunihiko (Frontiers in Public Health, 2023)
Introduction High stress at work is associated with negative health outcomes for workers, making stress prevention a critical challenge. Overtime work is an influential stress factor. This study, therefore, aimed to longitudinally evaluate how stress increased depending on changes in working hours among Japanese white-collar workers. Methods We targeted 3,874 participants who were full-time workers and were recognized as having low stress in a web-based cohort in 2018 (T1) and 2019 (T2). We performed univariate and multivariate logistic regression with the following variables: years of experience, years of education, medical background, income, and roommates. Results We observed a greater increase in stress among female who worked 41–50 h per week at T1 and more than 50 hours per week at T2, and those who worked more than 50 h per week at T1 and 35–40/41–50 h per week at T2, compared to those who worked 41–50 h per week both at T1 and T2, with odds ratios (ORs) and 95% confidence intervals (95% CI) of OR = 2.09, 95% CI (1.18, 3,70); OR =1.86, 95% CI (1.14, 3.03), respectively. However, no association between change in working hours and stress was found among male. Discussion These results show that reducing stress requires decreasing working hours as well as identifying factors that lead to high stress.